1975
DOI: 10.1161/01.res.37.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sympathetic denervation on smooth muscle cell proliferation in the growing rabbit ear artery.

Abstract: The effect of sympathetic denervation on the uptake of 3 H-thymidine ( 3 H-Tdr) into the ear artery of a growing rabbit was studied in vitro and in vivo. Uptake into the right artery was compared with that into the left 2 and 3 weeks after left superior cervical ganglionectomy in 4-week-old rabbits. Denervation was confirmed by the absence of catecholamine fluorescence. The total uptake of 3 H-Tdr was determined by scintillation spectrometry, and its distribution in the artery wall was studied by light microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
2

Year Published

1979
1979
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(68 citation statements)
references
References 17 publications
1
65
0
2
Order By: Relevance
“…For example, increased sympathetic innervation (Head, 1991) or exogenous elevation of plasma catecholamines (Stewart et al, 1992) has been associated with vascular smooth muscle hypertrophy in vivo. In addition, sympathetic denervation of blood vessels through mechanical (Bevan, 1975), chemical (Fronek et al, 1978), or immunological (Lee et al, 1987) methods results in decreases in DNA synthesis and cell number. The addition of catecholamines to vascular smooth muscle cell cultures increases DNA (Nakaki et al, 1990) and protein synthesis (Chen et al, 1995;Hu et al, 1999), as well as cell growth (Blase and Boissel, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased sympathetic innervation (Head, 1991) or exogenous elevation of plasma catecholamines (Stewart et al, 1992) has been associated with vascular smooth muscle hypertrophy in vivo. In addition, sympathetic denervation of blood vessels through mechanical (Bevan, 1975), chemical (Fronek et al, 1978), or immunological (Lee et al, 1987) methods results in decreases in DNA synthesis and cell number. The addition of catecholamines to vascular smooth muscle cell cultures increases DNA (Nakaki et al, 1990) and protein synthesis (Chen et al, 1995;Hu et al, 1999), as well as cell growth (Blase and Boissel, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that adrenergic neurons may exert a trophic influence on vascular smooth muscle. 20 Exposure to elevated levels of renin-angiotensin-aldosterone 21 or other humoral factors 22 " might in some way alter the composition of vessel walls to increase wall-to-lumen ratio. Clearly, the influence of such systemic factors must be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…These results could be explained by the release of a trophic substance from sympathetic nerves which acts on adenylate cyclase resulting in the production of cyclic AMP, which promotes differentiation, delaying dedifferentiation and proliferation. Further factors may be involved in the regulation of smooth muscle proliferation in vivo, since Bevan (1975) has shown that sympathetic denervation of the ear aretery in the young rabbit results in a reduction in the number of dividing cells compared with the control side, suggesting that the presence ofnerves enhances proliferation.…”
Section: (B) Prejunctional Neuromodulationmentioning
confidence: 99%